Research Progress on Agricultural Equipments for Precision Planting and Harvesting - Yongjian Wang; Hua Li; Xuebin Feng (Agriculture, 2025)
As the global population continues to grow, arable land resources are becoming increasingly scarce, climate change is intensifying, and the number of people employed in agriculture continues to decline; agricultural production is facing the dual pressures of yield enhancement and sustainable resource utilization [...]